"They don't really get heard": A qualitative study of sibling involvement across two forms of family-based treatment for adolescent anorexia nervosa. Issue 4 (4th July 2018) - van Langenberg, Tanja; Duncan, Rony E.; Allen, J. Sabura; Sawyer, Susan M.; Le Grange, Daniel; Hughes, Elizabeth K.
ABSTRACT: Little is known about the involvement of siblings in family-based treatment (FBT) for anorexia nervosa (AN). To explore the experience of families, adolescents who had completed FBT, their siblings, and parents were interviewed. Siblings reported that involvement in FBT enhanced their understanding of anorexia and that they supported their family in various ways. While siblings often wished they had attended more sessions, there was no consensus among parents and patients regarding sibling attendance and many were concerned about potential negative impacts on siblings. Clinicians should discuss sibling roles and expectations early in FBT and work actively with families to address concerns.